Composición química de la madera de Zchizolobium parahyba (Vell.) S.F.Blake (Pachaco) de una plantación de la Quinta Experimental El Padmi, provincia de Zamora Chinchipe - Quito Torres, Jhulissa Gabriela (2019)
The native species Schizolobium parahyba (Vell.) S.F. Blake with common name Pachaco, has an economic and ecological importance, widely used for plywood, furniture or interior carpentry, doors and toys, in addition to finding a potential as the production of pulp paper and biofuel production for bioethanol. According to this context it is important to generate information on the chemical composition of S. parahyba wood and at the same time relate the composition of the wood (ash, extractive, lignin and holocellulose) with the properties of the soil (pH, N, P, K). In order to study the composition of the species, six individuals were chosen from the Quinta Experimental “El Padmi”; of Zamora Chinchipe province, from which two to three slices of wood were extracted from the main trunk, then converted to flour and later the analysis of ash, extractive, lignin and hemicellulose of each sample was carried out. In order to analyze the soil, six soil samples were collected from the place where the analyzed individuals grew and then the level of pH, nitrogen, phosphorus and potassium was analyzed. The method used in the investigation is experimental, which was applied a non-parametric test of Kruskal-Wallis with Dunn Test on wood composition and soil properties. To relate the two variables, wood and soil, a bivariate Spearman correlation was applied which is a nonparametric test. The chemical composition of the wood resulted in holocellulose (66,524%) is the highest content, followed by lignin (30,466%), these two compounds are considered to be the most abundant in wood; the extractive content (1,393%) and ash (1,425) are in smaller proportions. The soil where the individuals grew is acid (5,28) with a medium nitrogen level (43,68 ppm), low phosphorus (12,56 ppm) and medium potassium (148,52 ppm). The relationship between each of the contents of the chemical composition of the wood and each of the chemical properties of the soil resulted in five relationships, which two are positive correlations (pH - lignin with a significance of 0,046 and nitrogen - holocellulose with a significance of 0,001) and three are negative correlations (pH - holocellulose with a significance of 0,0032, nitrogen - extractive with a significance value of 0,049, and nitrogen - lignin with a significance of 0,002). In addition to phosphorus and potassium, they did not yield any relation to the composition of the wood, since their significance level was greater than or equal to 0,05. Keywords: Ash, Extractive, Lignin, Hemicellulose, Soil analysis, Schizolobium parahyba, Relationship between chemical composition of wood and soil.